Pulling out the fishes caught - Mumbai Archive Project Team (Jio Institute, 2024)
The waters off the coast of Mumbai, located in the Arabian Sea, are rich in marine biodiversity and support a diverse range of fish species. Some of the various types of fish commonly caught in these waters include the Kingfish, also known as surmai, mackerel (bangda), pomfret (paplet), Bombay duck (bombil), sardines (tarli), red snapper (rane), cuttlefish (kanphoda), and prawns (jhinga). Exotic species, like sharks, tuna, lobsters, squids, and oysters, are also sold at the markets.